Tempo de secagem de árvores de Eucalyptus dunnii e ajuste das facas do picador na qualidade de cavacos para fins energéticos - Nogueira, Dâmaris Figueiredo Billo (2019)
The aim of this research was to evaluate the effect of the drying time of trees in the field and the adjustment of chopper knives on the quality of the Eucalyptus dunnii chips produced for the energy supply of boilers. The research was carried out at the cooperative Castrolanda, Castro - PR, at the planting of E. dunnii with seven-yearsold. Nine different types of chips were evaluated, resulting from the interaction between three tree drying periods and three adjustments of chopper knives. It was studied moisture, basic and bulk densities, ash content, upper, lower and useful calorific powers, fuel value index and chip particle size. An energy quality index for the chips was proposed as a parameter of comparison. The chips have basic density of 0.506 g/cm³ and upper and lower calorific powers equal to 4543.667 kcal/kg and 4219.667 kcal/kg. The moisture content differed significantly between the treatments, inversely proportional to the drying time. The ash content also showed a significant difference; however, it was not possible to observe a behavior shape. The useful calorific value and the fuel value index differed among the treatments due to the moisture of the wood, presenting a positive linear relationship; however, the fuel value index proved to be more efficient than the useful calorific value in the energy evaluation of the material. There were significant differences in granulometry and bulk density due to the different adjustment of chopper knives and drying time of the material. All the chips produced with 90 days of drying of the trees are energetically inefficient. The chip produced with 150 days of drying and with chopper adjustment with 4 knives plus 1 chock was the best. Considering the material with 120 days of drying, the chopper adjustment with 4 knives is what provides a chip of quality similar to the best treatment. Considering different moisture of tree to be chipped, aiming at keeping the same quality average, different knife adjustments must be adopted in the chopper.